Social and professional adaptation of transferred to reserve military servicemen as an object of financial support (World of finance, 2019)
Introduction. Nowadays there are no active governmental instruments to finance the activities associated with social and professional adaptation of former military servicemen. The implementation of such programs is mainly carried out at the expense of limited foreign assistance. Insufficient elaboration of theoretical fundamentals and practical aspects of financial supply to sustain the mentioned adaptation in Ukraine predominantly explain it.Objectives. One has to identify the semantic differences in scientific approaches to determination of essence of social and professional adaptation of transferred to reserve servicemen, suggest authentic definition of this notion from the viewpoint of its financial supply, systemize, generalize and deepen the theoretical & conceptual fundamentals of financing the mentionedabove events and programs of adaptation.Results. The author critically analyzed the number of definitions of social and professional adaptation of transferred to reserve servicemen and specified the structure of mentioned adaptation due to its main components. The updated definition of social and professional adaptation of transferred to reserve servicemen as an object of financing was determined. On the basis of generalized global and national experience there was developed a typology of financial sources for social and professional adaptation of former servicemen according to three criteria: level of formation, location and financing model. The author conditionally grouped four types of models of its financing due to available financial sources: centralized (budget), decentralizedendogenous, decentralized-exogenous and integrative (mixed). The author has also substantiated the fact that decentralized-exogenous model of financing of social and professional adaptation of former servicemen prevailed lately in Ukraine and identified its peculiarities and disadvantages.Conclusion. The suggested typology of financial sources for social and professional adaptation of transferred to reserve servicemen facilitates selection of optimal financial sources and models taking into account the national specificity. Under modern domestic conditions of social and economic development it is recommended to apply the integrative (mixed) model of financing that is based on the principle of social partnership and assumes the participation of all economic sectors in financing of program events of social and professional adaptation of transferred to reserve servicemen: municipal, business and non-governmental (public) ones